Pengaruh Model Advance Organaizer (AO) Berbasis Pembelajaran Bermakna Ausubel Terhadap Penguasaan Konsep Fisika Peserta Didik - Istiarini, Yunita; Wahyudi, Wahyudi; Rokhmat, Joni; Zuhdi, Muhammad (Universitas Hamzanwadi, 2023)
This study is aimed to determine the effect of Ausubel meaningful learning-based advance organaizer (AO) model on the physics-mastery abilities of concepts. This study is an experimental research with pretest and posttest only. The sampling technique was purposive sampling in which class XI MIPA 1 as the experimental class and XI MIPA 4 as the control class. The experimental class was treated with Ausubel meaningful learning-based advance organaizer (AO) model, while the control class was given a usual learning. Data on mastery of physics concepts with five alternative answers considering tests of validity, reliability, differentiation, level of difficulity and analysis of distractor. Based on the research results, the average posttest score for the experimental class was 74,36 while the control class was 64,30. The data tested for homogeneity and normality to conduct hypothesis testing using independent polled variant with of 2,81. Hypotesis test analysis shows that is accepted and is rejected, so it can be concluded that there is an effect of the Ausubel meaningful learning-based advance organaizer (AO) model on the physics-mastery abilities of concepts.